1973
DOI: 10.1139/v73-601
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen–Water Deuterium Exchange over Graphon Supported Group VIII Noble Metals

Abstract: Specific activities of Group VIII noble metals supported on Graphon have been determined for hydrogen-water deuterium exchange. Metal surface areas, which are required to calculate specific activities, were measured by hydrogen chemisorption, and by reaction of hydrogen with chemisorbed oxygen. For the second triad metals, ruthenium, rhodium, and palladium, and in the temperature range 140 to 225 "C, the variation of activity was R u < R h > Pd. For the third triad metals, osmium, iridium, and platinum, the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…At the A-B site, H,O adsorption is also possible (eq. [5]); the adsorption competes with the adsorption of D, and the adsorptive state is stable because of the high value of the heat of adsorption. Then the adsorbed D2 at A-B exchanges with H from S-H, producing DH and leaving D adsorbed at A-B and site S (eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the A-B site, H,O adsorption is also possible (eq. [5]); the adsorption competes with the adsorption of D, and the adsorptive state is stable because of the high value of the heat of adsorption. Then the adsorbed D2 at A-B exchanges with H from S-H, producing DH and leaving D adsorbed at A-B and site S (eq.…”
Section: Discussionmentioning
confidence: 99%
“…Coefficients in the denominator are equivalent to the adsorption equilibrium constants for reactions [ I ] and [5]. The equilibrium equation can be expressed as follows (29), c a fa…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter may be illustrated by the synthesis of [4,4,5, H]TLCK (41) (Figure 4.15). Complete reduction to the saturated compound is easily accomplished over palladium or platinum catalysts.…”
Section: Tritiation Of Carbon-carbon Multiple Bondsmentioning
confidence: 99%
“…Earlier, studies of 2 HHO-H 2 exchange catalyzed by supported 4 and unsupported 5 metals showed that their catalytic potency increased in the order Pd < (Ir, Rh, Ru, Os) < Pt; the potencies of the metals in parentheses varied relative to each other depending on the support. Earlier, studies of 2 HHO-H 2 exchange catalyzed by supported 4 and unsupported 5 metals showed that their catalytic potency increased in the order Pd < (Ir, Rh, Ru, Os) < Pt; the potencies of the metals in parentheses varied relative to each other depending on the support.…”
mentioning
confidence: 99%